(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
With economic recoveries slowing, COVID-19 uncertainties and disruptions continuing, and worsening fiscal capacity, the outlook for food and nutrition security for many low- and middle-income farmers and their livelihood is of significant concern. The study analyzed the effect of COVID-19 lockdown restriction on rural household food security and livelihood activities of arable crop farmers in Yenagoa Local Government Area of Bayelsa State, Nigeria. Data were collected through well-structured questionnaire from 100 arable crop farmers. Data were analyzed using simple descriptive and inferential statistical tools. The result showed that fever (x=3.8), cough (x=3.1), shortness of breath (x=3.5), headache (x=3.5), sore throat ( x=3.3) and congestion or running nose (=3.2) were perceived COVID-19 symptoms. Transportation (tricycle and taxi driving) (x=3.7), arable crop farming (x=3.4), handicraft (x=2.5), oil palm farming (x=3.4), fish farming (x=3.2), vegetable farming (x=3.4) and snail farming (x=3.1) were livelihood activities affected by COVID-19 movement restriction. Food availability (x=2.9), feeding efficiency/sufficiency (x=2.6), economic access to food (=2.5) and food quality (=2.5) were food status of the sample arable crop farmers. The regression result showed that the coefficient of COVID-19 movement restriction (2.531) was positive and statistically significant at 1%. The study concluded that COVID-19 movement restriction significantly affected food security status and livelihood activities of arable crop farmers negatively. Hence, the study recommended effort should be made by government and other agricultural agencies to establish food storage, preservation and processing facilities so that during movement restrictions farmers can have access to food and to avoid malnutrition for the aged farmers...